Serum leucine as a potential biomarker of insulin resistance in diabetic, prediabetic, and leucine-supplemented individuals - Ahmed Omar, Asmaa; Ibrahim Jewzali, Jwan (Zanco Journal of Medical Sciences (ZJMS), 2026)
Background and objective: Diabetes Mellitus type 2 (T2DM) represents a serious risk to public health known as hyperglycemia. High levels of serum leucine a branched chain amino acid have been associated with early insulin resistance and metabolic imbalances. This study investigates the relationship between serum leucine levels and insulin resistance, and to evaluate its potential as a biomarker alongside standard blood sugar markers in diabetic, prediabetic, and leucine-supplemented individuals undergoing training. Methods: A cross-sectional study, conducted at the (Galiawa hospital for diabetes and endocrinology and (AKA Fitness) center)/ Erbil city / Iraq. A total of 155 participants, aged between 30 and 69, were included, composed of 46 with T2DM, 38pre-diabetic patients, 36 non-diabetic and 35 healthy young active training individuals who received leucine supplementation. Data was collected by interview questionnaire about; sociodemographic, life style and results of biochemical tests. Results: High levels of serum Leucine were significantly increase with age, obesity (OR=2.4, 95% CI. 1.7 - 2.8) and increased risk of high fasting blood sugar (OR=1.14,95% of CI 1.09-1.18), HbA1c (OR=1.24, 95% of CI 1.12-1.37), and insulin resistance (OR= 1.06, 95% of CI 1.02-1.1) in diabetic and prediabetic. Excessive supplementation caused excess serum leucine levels and increase potential insulin resistance (OR=1.3, 95% CI I,07-1.6) with advancing age. Conclusion: High serum leucine levels can cause insulin resistance in elderly, obese, prediabetic, and diabetic patients, suggesting its potential use as a biomarker for early diagnosis. A low dose of leucine supplementation should be considered in individuals undergoing training.